The effect of withholding salt on the growth and condition of steers. - Smith, E.F.; Parrish, D.B.; Splitter, E.J. (Kansas Agricultural Experiment Station, 2012)
This test was to find what effect the withholding of salt has on the performance of steers on either fattening rations or wintering rations. Forty-two head of good quality Hereford steer calves were used in the test. There were four lots, 10 head to each lot, except that one lot contained 12 head. Two of the lots were full-fed grain and two of the lots were fed wintering rations. For the two lots receiving wintering rations, the test was determined May 2, 1951. The two lots on a full feed of grain were fed until July 9, 1951. The two lots on a full feed of grain were fed until July 8, 1951. A feedstuff analysis of the feeds used in the test may be found on page-of this bulletin.
Keywords: Beef; Salt; Performance; Steers